Illocutionary Performance and Objective Assessment in the Speech Act of Arguing - Corredor, Cristina (Informal Logic, 2021)
This paper endorses a view of argumentation and arguments that relates both to a special type of speech action, namely, the performance of speech acts of arguing. Its aim is to advance an analysis of those acts that takes into account two kinds of norms related to their correct performance, namely, felicity conditions and objective requirements related to the “correspondence with the facts.” It assumes that the requirement that certain objective conditions be satisfied is among the set of felicity conditions of speech acts of arguing. Taking this into account helps clarify the position and role of warrants in the performance and assessment of these acts.